Guinea pigs in balance: impact of the probiotic diet on the pH, microbiota and productive performance of guinea pigs - Cuenca-Condoy, Mercy; Campos-Murillo, Nathalie; Quinteros-Rodas, Wilson; Miranda-Yuquilema, José (Frontiers in Animal Science, 2026)
The study was conducted in two phases. In the first phase, the intestinal microbiota was characterised, the pH of the gastrointestinal tract (stomach, duodenum, jejunum, ileum and caecum) was determined, and intestinal morphometric variables were analysed: length, width and density of villi, as well as depth of Lieberkühn crypts in the small intestine. A total of 210 weaned guinea pigs of improved genotype were used, distributed into three dietary treatments: Alf (green alfalfa forage), Alf + BLC (green alfalfa forage plus balanced diet), and BLC (balanced diet). In Alf, 30 guinea pigs were distributed into three groups, and in Alf + BLC and BLC, nine groups/treatment were established, with 10 guinea pigs assigned per group. In the second phase, treatments Alf + BLC and BLC were supplemented with a probiotic mixture enriched with vitamins, minerals and amino acids at three inclusion levels (0, 0.5 and 1%), assigning three groups per level, while T1 remained as a control. The effect of these diets on intestinal morphometry variables and production parameters (feed intake, weight gain and feed conversion) was evaluated. Gastrointestinal pH was measured using a pH meter; microbiota was identified by mass spectrometry, and intestinal morphology was analysed by histological techniques. Results showed significant differences (p < 0.05) in gastrointestinal pH among diets, with concentrate feeding leading to a more alkaline environment. Microbial composition also varied according to diet, with Escherichia coli and Staphylococcus vitulinus predominating after weaning. Intestinal morphology was influenced by both age and type of diet, with probiotic supplementation enhancing villus length and density in the small intestine, while higher doses increased villus depth. Productive performance improved in guinea pigs receiving a mixed diet with 0.5% fortified probiotics, which showed greater weight gain, feed intake and better feed conversion. In conclusion, dietary composition and probiotic supplementation modulated gastrointestinal conditions, microbial communities and intestinal structure, resulting in improved growth performance. These findings suggest that gastrointestinal pH influences microbial composition, productive efficiency, and immune health, highlighting the importance of balanced nutrition and the use of probiotics to optimise health and performance in production guinea pigs.